A proibição de raptar alguém: estudo das formulações jurídicas em Ex 21,16 e Dt 24,7 - Santana, Elton da Silva (2022)
The present research proposes to study two legal formulations, as a poetic configuration, contained in the Pentateuch (Ex 21,16 and Dt 24,7) that, aim at the issue of human trafficking and the process of enslavement of kidnapped people. These are laws composed during the first millennium BC, within the scope of biblical Israel, which promote a certain theological reflection, within a very concrete context. Human trafficking is, without a doubt, a “great evil” in our midst. It not only hurts the dignity of those who are subjected to such a situation but ends up hurting all of humanity. Since it was ratified on December 12, 2018, the Palermo Protocol, within the framework of the United Nations (UN), has decisively contributed to the discussion and fight against this very serious crime. Pope Francis has been personally committed to raising awareness of this issue, whether in the Church or in society as a whole, not only making a dicastery more aware of this reality, as pointed out in several speeches, messages and documents that “cry” of the kidnapped people have reached the heavens. Therefore, it is an ethical duty of the Christian, enlightened by the divine word, but also of all humanity, to prevent, welcome and combat this tragic situation to which millions of people are subjected and exploited throughout the world